Structure-based Functional Study Reveals Multiple Roles of Transmembrane Segment IX and Loop VIII–IX in NhaA Na(+)/H(+) Antiporter of Escherichia coli at Physiological pH - Tzubery, Tzvi (American Society for Biochemistry and Molecular Biology, 2008)
The three-dimensional crystal structure of Escherichia coli NhaA determined at pH 4 provided the first structural insights into the mechanism of antiport and pH regulation of a Na(+)/H(+) antiporter. However, because NhaA is activated at physiological pH (pH 6.5–8.5), many questions pertaining to the active state of NhaA have remained open including the structural and physiological roles of helix IX and its loop VIII–IX. Here we studied this NhaA segment (Glu(241)–Phe(267)) by structure-based biochemical approaches at physiological pH. Cysteine-scanning mutagenesis identified new mutations affecting the pH dependence of NhaA, suggesting their contribution to the “pH sensor.” Furthermore mutation F267C reduced the H(+)/Na(+) stoichiometry of the antiporter, and F267C/F344C inactivated the antiporter activity. Tests of accessibility to [2-(trimethylammonium)ethyl]methanethiosulfonate bromide, a membrane-impermeant positively charged SH reagent with a width similar to the diameter of hydrated Na(+), suggested that at physiological pH the cytoplasmic cation funnel is more accessible than at acidic pH. Assaying intermolecular cross-linking in situ between single Cys replacement mutants uncovered the NhaA dimer interface at the cytoplasmic side of the membrane; between Leu(255) and the cytoplasm, many Cys replacements cross-link with various cross-linkers spanning different distances (10–18Å()) implying a flexible interface. L255C formed intermolecular S–S bonds, cross-linked only with a 5-Å cross-linker, and when chemically modified caused an alkaline shift of 1 pH unit in the pH dependence of NhaA and a 6-fold increase in the apparent K(m) for Na(+) of the exchange activity suggesting a rigid point in the dimer interface critical for NhaA activity and pH regulation.